PHARMACOGNOSTIC EVALUATION AND PHYTOCHEMICAL STUDIES ON THE STEMS OF JASMINUM SAMBAC LINN. - Gupta, Neha; Ranjan, *Vadi; Bansal, Mahipal (AYUSHDHARA, 2017)
Jasminum sambac (L.) Aiton (Family: Oleaceae), an ornamental plant extensively used in perfumery and religious purposes, is a herb which shows shrub-like appearance after two years. It is locally known as ‘Motia’ and produces white flowers with a very pleasant fragrance. Traditionally Jasminum species has been used to treat dysmenorrhoea, amenorrhoea, ringworm, leprosy, skin diseases and also as an analgesic, antidepressant, anti-inflammatory, antiseptic, aphrodisiac, sedative, expectorant. The aim of the present studies was to establish standardization parameters for the authentication and quality control of the stems of Jasminum sambac linn. So the pharmacognostical study and parameters related to physico-chemical properties have been evaluated as per WHO guidelines. Preliminary phytochemical screening in different solvents showed the presence of carbohydrates, starch, glycosides and steroids. Total ash, acid insoluble ash, water soluble ash, ethanol soluble extractive and water soluble extractive values were found to be 6%, 1%, 4%, 5.6% and 12.8% w/w respectively. Microscopic studies of transverse section of stem of Jasminum sambac stems showed the presence of covering and glandular trichomes, cortex, sclerenchymatous cells, phloem, lignified xylem, medullary rays, pith parenchymatous cells and lignified fibre cellular bundles. Powder microscopy of Jasminum sambac Linn. stem showed the presence of parenchymatous cells, trichomes, stomata, pitted vessels, lignified fibre cells, lignified fibre bundles. The results of the study can serve as a valuable source of information by providing suitable standards for identification of this plant material and can also be useful in setting some diagnostic indices for the identification and preparation of a monograph of the plant.